2017
DOI: 10.1371/journal.pone.0174274
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in NEPH3 gene confers high risk of renal failure in primary hematuric glomerulopathies. Evidence for predisposition to microalbuminuria in the general population

Abstract: BackgroundRecent data emphasize that thin basement membrane nephropathy (TBMN) should not be viewed as a form of benign familial hematuria since chronic renal failure (CRF) and even end-stage renal disease (ESRD), is a possible development for a subset of patients on long-term follow-up, through the onset of focal and segmental glomerulosclerosis (FSGS). We hypothesize that genetic modifiers may explain this variability of symptoms.MethodsWe looked in silico for potentially deleterious functional SNPs, using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
2
21
1
Order By: Relevance
“…This fact supports the use of LOAN as an alternative term to describe patients with thin basement membranes who can be complicated by proteinuria and decline of kidney function on long follow up, perhaps with the effect of genetic modifiers . For 3 such putative modifiers (2 in the NPHS2 gene [podocin] and 1 in the NEPH3 gene [filtrin]) co‐inherited with a COL4A3 mutation, functional cell culture studies were also supportive . In the present cohort none of the patients examined carried a high risk modifier allele, most probably due to their low population frequency.…”
Section: Discussionsupporting
confidence: 79%
“…This fact supports the use of LOAN as an alternative term to describe patients with thin basement membranes who can be complicated by proteinuria and decline of kidney function on long follow up, perhaps with the effect of genetic modifiers . For 3 such putative modifiers (2 in the NPHS2 gene [podocin] and 1 in the NEPH3 gene [filtrin]) co‐inherited with a COL4A3 mutation, functional cell culture studies were also supportive . In the present cohort none of the patients examined carried a high risk modifier allele, most probably due to their low population frequency.…”
Section: Discussionsupporting
confidence: 79%
“…In functional cell culture experiments, the alternative variant proteins impaired the interaction with other slit diaphragm partners and interfered with normal trafficking, demonstrating perinuclear staining . More recently we reported on the putative predisposing role of a variant in the NEPH3 gene (filtrin), also a component of the podocyte slit diaphragm . Patients carrying heterozygous COL4A mutations and co‐inheriting the variant NEPH3 ‐p.Val353Met had an increased risk to progressive kidney failure.…”
Section: Primary Mutations and Genetic Modifiers As Examples Of Pseudmentioning
confidence: 94%
“…Importantly, genetic epidemiology studies combining the general population cohorts of Framingham, KORAF4 and SAPHIR studies (11 258 individuals), revealed significant association with microalbuminuria in homozygous subjects 19 (Figure 2).…”
Section: Primary Mutations and Genetic Modifiers As Examples Of Psementioning
confidence: 98%
See 2 more Smart Citations